2017
DOI: 10.1097/coc.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Prostate Cancer Patients Who Exhibit Biochemical Failure Despite Salvage Radiation Therapy After Radical Prostatectomy

Abstract: Extended follow-up demonstrates that despite SRT failure, PCSS remains high in select patients. Early failure (≤1 y after SRT) predicted for significantly worse outcome and may represent a subgroup with more aggressive disease that may be considered for further prospective clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Although SRT allows to achieve a satisfactory long-term overall survival (OS) of 13.6 years, a second BR may occur in 50% of patients. 6 Therefore, it is critical to identify patients undergoing SRT that necessitate additional treatments. Analysis of the efficiency of second or third line hormonal treatment for PC patients relapsed after hormone therapy, revealed the effectiveness of nonsteroidal antiandrogens as alternative therapies, particularly for second line responders, whose survival was significantly higher than nonresponders, indicating a potential predictive prognostic value for second line responsiveness and supporting the concept that second line responders, although androgen independent, are still hormonally sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Although SRT allows to achieve a satisfactory long-term overall survival (OS) of 13.6 years, a second BR may occur in 50% of patients. 6 Therefore, it is critical to identify patients undergoing SRT that necessitate additional treatments. Analysis of the efficiency of second or third line hormonal treatment for PC patients relapsed after hormone therapy, revealed the effectiveness of nonsteroidal antiandrogens as alternative therapies, particularly for second line responders, whose survival was significantly higher than nonresponders, indicating a potential predictive prognostic value for second line responsiveness and supporting the concept that second line responders, although androgen independent, are still hormonally sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the series with the longest followup (median 126 months), only 56% experienced BCR after salvage EBRT; OS averaged 13.6 years from the time of PSA failure. 8 Conversely, we might also interpret the present results as showing the benefit of EBRT in a majority of patients presenting with persistent or recurrent prostate cancer.…”
Section: Discussionmentioning
confidence: 45%
“…SV size can also play a significant role in diagnosis and treatment of prostate cancer. A recent study of markers for aggressive prostate cancer in 406 patients found that SV invasion (SVI) by localised prostate cancer is associated with a worse post-operative recurrence-free survival, a finding corroborated by other studies (Mitchell et al, 2016;Troyer et al, 2015;Ying et al, 2015). However, while MRI is reliable in detecting extracapsular extension of prostate cancer, it remains suboptimal at detecting SVI.…”
Section: Discussionmentioning
confidence: 74%